Compliance in corporate culture: codes of ethics and conduct of consultants - V. I. Aleshnikova (State University of Management, 2021)
For a long time, the point of view on compliance as a set of initiatives aimed at preventing illegal actions dominated. Currently, an extended interpretation of compliance is becoming widespread, which should also cover the ethical aspects of doing business.During the analysis, it was found that ethical standards in consulting were formed simultaneously with the formation of the consultant profession. This allows us to draw a conclusion about the successful century-old practice of implementing ethical codes into the corporate culture of consulting firms. This article is a continuation of the authors’ research in the field of management consulting.The purpose of the study is to analyse the Russian and foreign experience of implementing ethical standards and compliance control in the field of management consulting. The methodological basis of the research is the methods of logical, comparative, expert analysis, marketing research. The informational basis of the research is regulatory legal acts, official websites and documents of consulting companies and professional associations of consultants, expert assessments and ratings of consulting firms.The article reveals an interconnected three-level system of international, national and intra-company standards of business ethics and professional practice; gives examples of reputational risks of well-known international consulting companies; justifies the role of consulting firms in the formation of the ethical structure of business. The practical significance of the study is to focus the attention of client companies on the need to familiarize themselves with the standards of ethics and business practices before concluding a contract with a consulting firm.